Characterization of a Prostate- and Prostate Cancer-Specific Circular RNA Encoded by the Androgen Receptor Gene - Jindan Luo; Yinan Li; Wei Zheng; Ning Xie; Yao Shi; Zhi Long; Liping Xie; Ladan Fazli; Dahong Zhang; Martin Gleave; Xuesen Dong (Elsevier, 2019)
The linear mRNAs transcribed under alternative RNA splicing and overexpression/amplification of the androgen receptor (AR) gene are poor prognostic biomarkers of castrate-resistant prostate cancer (PCa). Whether the AR gene also transcribes non-coding circular RNAs that are associated with PCa development and tumor progression remains unclear. Here, we identified and characterized an AR circular RNA, called circAR3, that is widely expressed in PCa cell models and prostate tumors. circAR3 can be secreted into culture media of PCa cell lines and is detectable in the serum from mice bearing PCa xenografts. In PCa patient tissues, circAR3 is highly expressed in benign prostate and hormone naive PCa but downregulated when tumors were treated with neoadjuvant hormone therapy and further reduced when tumors progressed to the castrate-resistant stage. However, circAR3 levels in plasma are extremely low in patients with benign prostate, are upregulated in PCa patients with high Gleason scores and lymph node metastasis, and become undetectable in men after radical prostatectomy. circAR3 does not affect AR signaling, PCa cell proliferation, and invasion rates. Our results demonstrated that the origin of the detectable plasma circAR3 is from the prostate/PCa. Plasma circAR3 may be developed to be a PCa biomarker to monitor PCa development and tumor progression. Keywords: prostate cancer, androgen receptor, circular RNA, circAR3, alternative RNA splicing, cell-free circular RNA, AR splice variant